Effectiveness of Medical Rehabilitation of Patients after a New Coronavirus Infection in a Day Hospital - Irina E.Mishina; Yulia V.Chistyakova; Eugenia V.Pchelintseva; Irina V.Mitryaeva; Svetlana O.Fokicheva; Elena V.Berezina; Denis S.Bendin (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
Aim. To investigate the prevalence of clinical manifestations of post-coronavirus syndrome and evaluate the effectiveness of medicalrehabilitation course in patients after new coronavirus infection (COVID-19) in a day care hospital, taking into account the severity ofthe disease course.Material and methods. At the first stage of the study, 203 residents of the Ivanovo region (140 women and 63 men) aged 40 to 80years who had a new coronavirus infection, who had no more than one year since the onset of the disease, were surveyed on thebasis of the Ivanovo State Medical Academy (ISMA) of the Ministry of Health of Russia. For this purpose, "COVID-19 Yorkshire RehabilitationScreening (C19-YRS)" telephone screening questionnaire was used, developed by groups of rehabilitation therapists from thetraining medical centers of the National Health Service of Great Britain to identify multisystem functional disorders of patients whohave suffered a new coronavirus infection, and to address the need for rehabilitation intervention. At the second stage, 54 patients(38 women and 16 men) aged 29-81 years were examined, who were admitted to the 3rd stage of rehabilitation in the departmentof medical rehabilitation of patients with somatic diseases of the ISMA Clinic after suffering a new coronavirus infection COVID-19.Among them, 3 groups were formed depending on the severity of the infection: 16 patients with a mild course of the disease madeup the 1st group, 20 patients who had a moderate course of coronavirus infection - the 2nd group, 18 patients with a severe courseof COVID-19 - 3rd group.Results. The questionnaire showed that COVID-19 survivors had a multisystem decrease in functioning, which was maximally pronouncedduring the first month from the onset of the disease and did not return to the baseline level for 6-12 months. The most significantdisturbances occurred with patients who, due to the severity of the condition, were treated in a hospital. The most lastingsymptoms were impaired exercise tolerance and increased fatigue, which had a significant impact on daily life. In patients admitted forrehabilitation, functional impairments and disabilities were detected regardless of the severity of the course of the new coronavirusinfection (COVID-19). In patients with a mild course of infection, they were manifested mainly by decreased tolerance to physical load,frequent disorders of sleep function, emotions, volitional and motivational functions, in some patients - by mild disorders of respiratoryfunction and cognitive impairment in the form of reduced volume of cranio-temporal memory. In patients with moderate and severeCOVID-19, against the background of impaired exercise tolerance function, sleep function, emotions, volitional and motivational functions,we mainly detected moderate and pronounced respiratory disorders, cognitive disorders, which were manifested by decreasedshort-term memory and attention concentration, increased attention exhaustion, and bradyphrenia. The functional disorders detectedin patients primarily led to limitation of their mobility in the form of walking for long distances, ability to self-care and household activities,ability to work, which before the disease did not cause difficulties for patients. Study of the indexes in dynamics showed the effectivenessof rehabilitation measures in improving the functions, regardless of the severity of the course of coronavirus infection.Conclusion. The findings of the present study justify the necessity of early complex rehabilitation of patients by multidisciplinary rehabilitationteam taking into account individually detected functional impairment. Individual rehabilitation program should be developedfor each patient taking into account the revealed problems on the basis of problem-oriented approach.